DETECCIÓN DE ANIMALES PORTADORES DEL VIRUS DEL CÓLERA PORCINO EN UNA GRANJA TECNIFICADA DEL VALLE DE LIMA - Camargo C., lván (2002)
The objective of this study was to identify animal carriers of the Hog Cholera virus (HCV) post vaccination in a well-managed pig farm ofLima valley. A total of 166 serum samples were collected from 166piglets between 6 and 7 weeks of age, vaccinated against Hog Cholera 15 days befare sampling. Specific HCV antibodies were detected using a blocking ELISA test. Eighty eight (146/166) of animals reacted positively against HCV; 3% (5/166) and 9% (15/166) of animals were considered suspects and negatives to antibodies, respectively. A second sample was collected 30 days after the first collection from suspect (n=5) and negative (n=15) animals. HCV was detected by direct inmunofluorescence test using cultivated lymphocytes. At the time of the second sampling, 14 out of20 animals stayed at farm. Antibodies were detected in 6 animals and 8 were negative, however 4 ofthe latter were positive to HCV The results showed that the frequency ofHCV carrier animals was 2.4% ( 4/166). The lack of antibodies and the presence ofHCV in lymphocytes after vaccination, suggested that those animals were persistently infected and HCV carriers.